Facility Management Challenges and Opportunities in the Malaysian Property Sector - Syed Mustapa, Syed Abdul Haris; Adnan, Hamimah; Jusoff, Kamaruzaman (2008)
Facilities Management (FM) is becoming an increasingly important factor in the built environment. In Malaysia, the field is still in its infancy. This paperwork aims to determine the extent of FM in Malaysia and reviews the changes in the property sector that may positively contribute to opportunities in FM and the challenges that need to be taken into account. In particular, this paper focuses on the changes that are taking place, both at the corporate and at government level. The paper considers issues arising in the local market based on personal observation and discussions with professionals in the property management sector in Malaysia. This review focuses on areas where FM is being actively implemented. This includes discussion on the types of property FM, the management method used and the extent of FM being adopted. The challenges and the opportunities in the local property and construction market are also discussed, specifically to understand the limits of growth for FM. FM is relatively new in Malaysia and much it’s the wider concept of FM of building management is still in the process of improving its maintenance management structure. Generally, Integrated Building Management Systems which require an integrated IT advancement and strategic management approach is widely being seen as the improvement of FM in Malaysia. This in fact is the closest definition for FM that is being understood in Malaysia. It may be concluded that until the property management industry fully matures it is unlikely that facility management will be widely practiced for some time in the Malaysian property sector.